Analisis Faktor-Faktor Yang Mempengaruhi Pemilihan Investasi Pada Generasi Z Di DKI Jakarta - Sita Noveni Raudha; Farah Margaretha Leon (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study aims to determine whether there is a significant relationship between risk aversion, risky investment intention, cognitive ability, financial literacy, and several control variables (age, gender, marital status, education level) with investment choice as a dependant variable. Using quantitative methods with a population of 2.7 millions generation Z in Jakarta and samples of 153 respondents who refer to men or women who live in DKI Jakarta and are aged 14-25 years. The data was obtained through a questionnaire survey which was tested with multiple linear regression. The results show that risk aversion and risky investment intentions affects investment choice with a significance value of less than 0.05. Therefore, with this research it is expected that the public and the government can realize the importance of knowledge about finance so that it will increase public knowledge about the importance of investing.Keywords: cognitive ability; financial behavior; financial literacy; investment choice; risk aversion